Evaluation of the denture impact on the palatal rugae: An original research - Sumeet Hardiya; G Jeevan Kumar; Manne Vimala Sai; Komal Rana; Disha Desai; Gaganpreet Kaur (Wolters Kluwer Medknow Publications, 2023)
Introduction: The palatal rugae may alter their shape based on the various physical pressures that they had to endure. This study's objective is to assess the various alterations in the palatal rugae parameters among the complete denture wearers. Materials and Procedures: Forty subjects in all were chosen for the study. The control group interventional groups had an equal number of participants who were further equally distributed based on gender. For all of the participants, mucostatic maxillary alginate imprints were taken, and gypsum castings were created. They were called at the scheduled intervals of 2, 6, and 12 months following the treatment. The models used during those recalls and all of the palatal rugae were examined under a microscope for quantity, length, form, orientation, and unifications. The unpaired t-test was used to statistically examine palatal rugae alterations. Results: Following the wear of the dentures, the experimental group's primary, secondary, and fragmented rugae all gradually shrank in length. In terms of statistics, the alteration solely affected primary rugae and was significant (P < 0.001). After a year of wearing dentures, a minimal change in rugae's form was noticed in the denture groups, but it was statistically not substantial (P > 0.05). Conclusion: Due to the prolonged mechanical stress the dentures placed on the palatal rugae, complete denture users saw a significant reduction in the length of their primary rugae. Rugae number, orientation, and unification were among the other criteria that did not change during the course of the study. Analysis of the palatal rugae may not be useful in identifying people wearing full dentures. However, in forensic investigations, rugae may act as an adjunct to other methods like fingerprints and DNA analysis.